Abroad technology: effect to the product quality at Pertubuhan Peladang Kawasan Segamat Tengah / Noor Azliza Abd Samad - Abd Samad, Noor Azliza (Faculty of Business and Management, 2011)
Nowadays the use of EM Technology is not the new things. Most of the agriculturists at the urban area already use this technology and gain in the production. But in the rural area, the use of this technology is new and do not know well by the agriculturist. Other than that, the information about the EM Technology also too little and this make the agriculturist at the rural area resist to change and shift to the new technology. The study will be used correlation method to see the relationship between dependent and independent variables. Product quality will be used as dependent variable and product performance, product features and product reliability when use EM Technology will be used as independent variables. Recommendations will be given on the potentials and opportunities to increase the use of EM Technology at the rural area in order to help the agriculturist to gain more in the future